FAKTOR PENERAPAN NORMATIF GREEN CONSTRUCTION PADA PEMBANGUNAN THE ALTON APARTEMEN - Rani Pranita; Mochamad Agung Wibowo; Broto Sunaryo (Politeknik Negeri Semarang, 2022)
Green Construction is a continuous movement to create quality construction. The government in responding to the management of the implementation of green construction issues regulations that are expected to become development guidelines. This study aims to identify the application of green construction in the implementation of the construction of The Alton Apartement to achieve the performance that has been determined with a rationalistic positivistic approach. The research methodology uses qualitative methods with in-depth interviews with triangulation to determine its validity. The result is the level of normative application of green construction in the implementation of apartment construction projects, three levels of application are obtained which show the results of the identification of the normative application of green construction. The level of implementation of III was 37% where these aspects have been carried out in a sustainable manner. The level of implementation of II reached 41%, where the implementation has been carried out well. The level of implementation of I is at 22%, which means that the implementation in the field has not been implemented properly.